Peningkatan Efesiensi Produksi Electric Arc Furnace Dengan Injeksi Oksigen Untuk Menghemat Biaya Energi Listrik Pada Industri Baja - Wardhana, Arief Wisnu (Jenderal Soedirman University, 2007)
The highest production in steel making process is the cost of melting in the Electric Arc Furnace (EAF). The higher the electricity cost , the higher the production cost would be. Some means have to be done , therefore, in the melting process, in order to achieve higher efficiency. One of them is by installing a water cooling panel system at the furnaceâs wall and roof. Another way is by chemical reaction through oxygen injection into EAF. The combination of the two will result in tap voltage at higher current and long arc setting. By obtaining higher power factor and long arc, we can achieve higher productivity and electricity cost saving. Experience and data shows that the power factor and long arc obtained can save up to 1.9 Kwh per Nm3 oxygen . Using the data, if oxygen were increased until 30N m3/ton , the fixed production cost would increased approximately 5 % for every increase of Rp.100,-/Kwh in electricity cost. Therefore, in order to stabilize the production cost, energy transformation capacity should be increased to become 130 MVA which is combined with an adequate oxygen injection management